The Influence of Live Streaming, Fear of Missing Out (FoMO), and E-WOM on Purchase Decisions in TikTok Shop - Ahmad Rifqi Alfarisi; Sukaris Sukaris (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the influence of Live Streaming, Fear of Missing Out (FoMO), and Electronic Word of Mouth (E-WOM) features on purchasing decisions on the TikTok Shop platform in Indonesia. TikTok Shop is a social commerce platform that combines entertainment elements with online shopping, which attracts consumers through innovative approaches such as Live Streaming, user reviews, and limited promotions. The study was conducted using a quantitative method by distributing questionnaires online to 100 TikTok Shop users. The data obtained were analyzed using multiple linear regression to test the influence of each independent variable (Live Streaming, FoMO, E-WOM) on purchasing decisions. The results showed that all three variables had a significant effect on purchasing decisions, with E-WOM having the greatest influence. These findings indicate the importance of user reviews and live product demonstrations in creating trust and encouraging impulse buying. The implication of this study is that business actors can optimize the Live Streaming and product review features to increase sales and build consumer loyalty.